An Improved Transducer Mount for Ground Vibration Measurements - Barman, Mohan; Coulter, John E. (Canadian Acoustics, 1981)
Standardization of soil vibration measurement has been an area of very limited consideration up until the last decade or so. To date measurement methodology has only been partially documented. The current demand for land in built up areas has led to building construction near, and on top of rail transportation corridors, and caused sufficient difficulties to demonstrate a requirement for reliable vibration measurement methods. This paper discusses transducer mounting methods for obtaining accurate soil vibration measurement. Proposed, is an inexpensive system believed to offer considerable advantage over current practices.